USULAN DESAIN STOPPER SEBAGAI ALAT BANTU PROSES GROOVING PADA PART SUCTION COVER POMPA SENTRIFUGAL TIPE Y DI PT X - Ricky Soleman Manikari; Steven Darmawan (Program Studi Teknik Mesin Universitas Tarumanagara, 2022)
Centrifugal pumps have a design consisting of an impeller rotor and an inlet channel in the middle. When the rotor of impeller rotates, the fluid will flow into the casing due to the centrifugal force. Suction Centrifugal pump casing is designed in the form of a diffuser that surrounds the pump impeller. This diffuser is more commonly known as the volute casing. In accordance with the function of the diffuser, the volute casing serves to reduce the flow velocity of the fluid entering the pump. The stopper is a fixture that is used as a support for the suction cover part during the grooving process. Stopper is used so that the surface turning results are not oval . Grooving is a process to form a groove on a workpiece by using a lathe or milling machine and others . To give the results of the groove surface on the suction cover, it is necessary to carry out a grooving process. The grooving process is used to smooth the grooves on the suction cover surface. However, because the diameter of the suction cover is quite large, an additional fixture is needed to support the suction cover so that it remains in an even position during the grooving process. The stopper is important thing in the process of grooving suction cover type E-100 50 with a spindle speed of 180 rpm. The dimensions of the proposed stopper are 155.88 mm long, 150mm wide, and 150m high. So this stopper fixture must be strong and stable during the machining process. The purpose of this paper is to propose a 3D fixture design during the process of grooving the suction cover E 100 50. This research was carried out theoretically using data machining and parts obtained during observation. Compilation of observational data in the form of images and strength analysis in 3 dimensions using Autodesk Fusion 360 software. The results of this study are divided into 2 parts, 3D design and strength analysis including von mises stress, displacement and safety factor. From the results of the simulation von mises in picture 8, it shows that the stress that occurs is 32.59 MPa at the most critical part. The critical part is the upper support section which is the center of support. From the results of the simulation displacement in picture 9 it shows that the change (displacement) in the design stopper maximum so that deformation occurs, which is indicated by a red color of 0.002668mm. Changes above 1mm the material will break. This shows that the shape and dimensions of the stopper are said to be in the safe category. From the picture of the results of thesimulation Safety Factor in picture 10, it shows that the value of the safety factor for a sufficient level of safety is 6.353. If it is less than the value of the safety factor, the material has been deformed or broken because the maximum stress is comparable to or greater than the yield strength of the material.